Constraints on Opera Surtitling: Hindrance or Help? - Rędzioch-Korkuz, Anna (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2018)
The article addresses the problem of constraints typical of opera surtitling, an audiovisual translation modality that seems rather neglected as far as the academic discourse is concerned. Although the term constraint may appear to have mainly negative connotations, it seems that the idea of a constraint may often prove helpful, since it may facilitate the process of translation by restricting the scope of possibilities and hence justify the chosen techniques. The article is meant to propose a classification of potential constraints on the surtitling process, including the constraint of a live performance, music, audience design or relevance, and the resulting implications for the whole process. It is argued that the awareness of the constraints operating in the process of drafting surtitles helps to understand the rationale behind this particular translation activity and consequently helps to draft good quality surtitles which serve their original purpose.